2011
DOI: 10.1038/cdd.2011.2
|View full text |Cite
|
Sign up to set email alerts
|

DAPK activates MARK1/2 to regulate microtubule assembly, neuronal differentiation, and tau toxicity

Abstract: Death-associated protein kinase (DAPK) is a key player in several modes of neuronal death/injury and has been implicated in the late-onset Alzheimer's disease (AD). DAPK promotes cell death partly through its effect on regulating actin cytoskeletons. In this study, we report that DAPK inhibits microtubule (MT) assembly by activating MARK/PAR-1 family kinases MARK1/2, which destabilize MT by phosphorylating tau and related MAP2/4. DAPK death domain, but not catalytic activity, is responsible for this activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 40 publications
0
64
0
Order By: Relevance
“…MAP1B is a key target of DAPK1 (46). DAPK1 also plays a key role in the regulation of cell morphology by bridging membrane proteins with the cytoskeleton (46,(70)(71)(72). Finally, unbiased loss-of-function studies have shown that DAPK1 is required specifically for proper subcellular localization of late/recycling endosomes (72), the vesicular compartment expanded in the apex of maturing ZCs, as described above.…”
Section: Discussionmentioning
confidence: 94%
“…MAP1B is a key target of DAPK1 (46). DAPK1 also plays a key role in the regulation of cell morphology by bridging membrane proteins with the cytoskeleton (46,(70)(71)(72). Finally, unbiased loss-of-function studies have shown that DAPK1 is required specifically for proper subcellular localization of late/recycling endosomes (72), the vesicular compartment expanded in the apex of maturing ZCs, as described above.…”
Section: Discussionmentioning
confidence: 94%
“…It is not clear for MARK1 and its close relatives what might be the second target analogous to septins. One intriguing possibility is death-associated protein kinase, which has been reported to relieve autoinhibition of MARK1 and MARK2 by binding to the ‘linker’ region [48] to modulate microtubule assembly and neuronal differentiation, and may do so in concert with KA1 domain engagement by anionic membrane surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Death-associated protein kinase (DAPK) inhibits microtubule assembly by activating MARK2. The death-associated protein kinase death domain but not catalytic activity is responsible for this activation by binding to the MARK2 spacer region, thereby disrupting an intramolecular interaction that inhibits MARK2 (35). PAK5, a neuronal member of the p21-activated kinase family, suppresses the activity of MARK2 (36).…”
Section: Discussionmentioning
confidence: 99%